Congenital urethral hypoplasia with urethral fistula without imperforate anus: Report of two cases - Kumar Basant; Sharma Shyam; Agrawal Leela (Wolters Kluwer Medknow Publications, 2008)
Two male children with ano/recto-urethral fistula without anorectal malformation were managed in our institute. These patients had variable clinical manifestations and associated anomalies including congenital urethral hypoplasia, renal agenesis and patent urachus. Both were treated successfully according to their status of disease-complexes. This is to discuss these rare cases and its management with review of the literature.